Termite mounds house a diversity of taxa in oil palm plantations irrespective of understory management. (5th February 2020) - Hood, Amelia S. C.; Pashkevich, Michael D.; Dahlsjö, Cecilia A. L.; Advento, Andreas D.; Aryawan, Anak Agung Ketut; Caliman, Jean‐Pierre; Naim, Mohammad; Head, Jason J.; Turner, Edgar C.
Abstract: We investigated the effects of oil palm understory vegetation management on termite mound activity and non‐termite inhabitants. We found a diversity of taxa, most of which were unaffected by understory management. Mound volume and termite activity had taxa‐specific effects on abundance. Preserving mounds in oil palm plantations will benefit biodiversity. Abstract in Indonesian is available with online material. ABSTRAK: Kami menyelidiki efek manajemen vegetasi lantai di perkebunan kelapa sawit terhadap aktivitas rayap dan penghuni selain rayap dalam gundukan. Kami menemukan beragam taksa, yang sebagian besar tidak terpengaruh oleh manajemen vegetasi lantai. Volume gundukan dan aktivitas rayap memiliki efek taksa spesifik terhadap kelimpahan. Mempertahankan gundukan di perkebunan kelapa sawit akan menguntungkan biodiversitas.